2018
DOI: 10.3389/fpsyg.2018.01008
|View full text |Cite
|
Sign up to set email alerts
|

Category-Based Learning About Deviant Outgroup Members Hinders Performance in Trust Decision Making

Abstract: The present research examines whether individuation and categorization processes influence trust decisions about strangers at first and across repeated interactions. In a partial replication of the study reported by Cañadas et al. (2015), participants played an adaptation of the multi-round trust game paradigm and had to decide whether or not to cooperate with unknown partners. Gender (Study 1a) and ethnicity (Studies 1b, 2, and 3) served to create distinct social categories among the game partners, whose reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 77 publications
(126 reference statements)
5
28
0
Order By: Relevance
“…Before data collection, we decided to run a minimum of 40 participants in each group, as in previous research using this paradigm (Telga et al, 2018). Accordingly, 41 older (24 men, mean age: 65.36, range: 60-86) and 41 younger (12 men, mean age: 21.78, range: 18-27) volunteers participated in the study in exchange for a financial compensation proportional to their performance in the task (€5.40 on average).…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Before data collection, we decided to run a minimum of 40 participants in each group, as in previous research using this paradigm (Telga et al, 2018). Accordingly, 41 older (24 men, mean age: 65.36, range: 60-86) and 41 younger (12 men, mean age: 21.78, range: 18-27) volunteers participated in the study in exchange for a financial compensation proportional to their performance in the task (€5.40 on average).…”
Section: Participantsmentioning
confidence: 99%
“…We expected the pattern of results in the learning phase to echo previous findings observed with gender and ethnic categories. In particular, Telga et al (2018) found that younger participants' learning about gender and ethnic outgroups is impacted by an outgroup homogeneity effect. In the present research, we also expected younger participants to show an outgroup homogeneity effect with age categories.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations